KEPEMIMPINAN PENDIDIKAN: MENGHADAPI DISRUPSI DAN VUCA DI MASA DEPAN - Wulansasi, Ajeng; Jauhari Ma’mun, Ahmad Aji (Managere: Indonesian Journal of Educational Management, 2019)
Disruption brings fundamental changes in almost all aspects of life, changes are made by small institutions that are more agile and distributed, taking over the role of incumbents established. Disruption in education is defined as a new way that shifts the old way that is less relevant, such as technology, perspectives, approaches, teaching processes, instructional media, forms of classrooms and others. The reality of change creates a state of VUCA (Volatile, Uncertain, Complex and Ambiguous) where the world is very dynamic and difficult to predict. The old form of leadership is no longer able to deal with current changes, new leadership characteristics must be developed to face the future, addressing the needs and problems that arise from the uncertainty and ambiguity of the current situation. The study aims to discuss current literature and research on the characteristics of future leaders that are appropriate for responding to change. It also provides an overview of future leadership and provokes the birth of thoughts on leadership issues, especially in the field of education. The method used in in this study is concept analysis which is a study of important concepts interpreted by users or implementers in a variety of ways. Data collection techniques used were a review study of books, literature, notes, and journals related to the theme discussed. The result show that educational leadership characteristics need to be developed in face with change and VUCA environment.